Structural transformation of Ukraine’s exports in the pandemic period - PIANKOVA, Оксана; RALKO, Олександра; SLOKVA, Марина (Ius Modernum, 2020)
Background. The erasing of the pandemic and its rapid spread all over the world has become a great challenge both for the global economics and for individual national economies. Analysis of recent research and publications. International organizations, including the WTO, IMF, FAO, are engaged in the actualization of the problem of levelingthe impact of the pandemic on the issue of debt, financial, food security. Scientists and practitioners are concerned about the consequences of the spread of COVID-19 for doing business and the ability to freely supply goods to foreign markets. However, the problem of transforming the structure of exports in the context of a pandemic remains poorly studied, controversial, and requires detailed consideration. The aim of the article is to study the transformation of the export structure, taking into account the geographic diversification of the supply of domestic goods and the adjustment of the commodity saturation of the country's export basket in the pre-pandemic and pandemic periods. Materials and methods. The study is based on the works of foreign and domestic scientists, materials of international and domestic organizations, enterprises data. In the process of preparing the article, the following methods were used: system-structural; statistical and graphic; abstract-logical. Results. The article contains investigation of the concept of transformationas an economic phenomenon, structural transformation of exports is considered as evolutionary and/or revolutionary change in the geographical vector of export development and/or optimization of the disproportion of the export basket under the influence of endogenous and exogenous determinants. The authors carried out the assessment of the structural transformationofthe economy according to the foreign economic approach, the transformation of the geographical and commodity structure of exports; investigated the dynamics of the currency structure of receipts for goods; defined the determinants of changes in the pre-pandemic and pandemic periods; made proposals for the further development of the structure of the domestic export basket; substantiated the need for anti-crisis post-pandemic development of exports. Conclusion. The pandemic became a catalyst for the problems of exporters, made them think about options for solving them through the formation of an anti-crisis policy and an immediate search for ways of anti-crisis post-pandemic development.